Properties of B4C-TiB2 ceramics prepared by spark plasma sintering - Jingzhe Fan; Weixia Shen; Zhuangfei Zhang; Chao Fang; Yuewen Zhang; Liangchao Chen; Qianqian Wang; Biao Wan; Xiaopeng Jia (中国物理B（英文版）, 2021)
By doping titanium hydride(TiH2)into boron carbide(B4C),a series of B4C+x wt％TiH2(x = 0,5,10,15,and 20)composite ceramics were obtained through spark plasma sintering(SPS).The effects of the sintering temperature and the amount of TiH2 additive on the microstructure,mechanical and electrical properties of the sintered B4C-TiB2 composite ceramics were investigated.Powder mixtures of B4C with 0-20 wt％TiH2 were heated from 1400 ℃ to 1800 ℃ for 20 min under 50 MPa.The results indicated that higher sintering temperatures contributed to greater ceramic density.With increasing TiH2 content,titanium diboride(TiB2)formed between the TiH2 and B4C matrix.This effectively improved Young's modulus and fracture toughness of the composite ceramics,significantly improving their electrical properties:the electrical conductivity reached 114.9 S·cm-1 at 1800 ℃ when x = 20.Optimum mechanical properties were obtained for the B4C ceramics sintered with 20 wt％TiH2,which had a relative density of 99.9±0.1％,Vickers hardness of 31.8 GPa,and fracture toughness of 8.5 MPa·m1/2.The results indicated that the doping of fine Ti particles into the B4C matrix increased the conductivity and the fracture toughness of B4C.